Spiritual Care in Patient with Cancer Pain: Literature Review - Maria, Riri; Waluyo, Agung; Khamarudin, Khamarudin (Indonesian Journal of Global Health Research, 2024)
Spiritual care for cancer pain is an intervention to address the spiritual needs of patients with cancer in managing pain. Despite numerous studies conducted in this area, the diversity of spiritual care interventions for cancer pain remains a challenge. Objective: This literature review aimed to identify spiritual care interventions for cancer patients in managing pain. Method: The database used Scopus, Pubmed, Proquest, Science Direct, and Google Scholar. The keywords used were “spiritual care” OR “spiritual therapies” OR “spiritual healing” OR “faith healing” OR “spiritual intervention” OR “religious intervention” AND “cancer pain” OR “cancer-related pain” OR “neoplasm-related pain” OR “oncology pain. The search was limited to articles published between 2011 and 2021, resulting in the identification of 6642 articles, which only 10 met the inclusion criteria. The selected articles underwent critical appraisal using JBI tools. Results: This literature review showed that the types of spiritual care interventions consist of yoga, psychoreligious intervention, mindfulness, music therapy, and therapeutic touch, and the primary outcomes of spiritual care are pain levels. Conclusions: This literature review showed the interventions were very diverse in all types of cancer. Therefore, a spiritual care intervention study on managing pain with a specific type of cancer is needed.